(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: This research aims to identify the compliance rate and factors related to hand hygiene compliance of of medical staff with hand hygiene regulations at Friendship Hospital clinical departments 2023. Research and methods: Cross-sectional study, established through observation and conducted survey by Google Form upon 421 medical staff who followed hand hygiene procedures out of 5061 hand hygiene possibilities. The data collection lasted from January until the end of December 2023. SPSS 22.0 was used in this paper for data entry and analysis. Results: The percentage of medical staff complying with regulated hand hygiene routines in general was 64.4%; the compliance rate among doctors was 59.1%, 65.4% for nurses, and 60.6% for students. The compliance rate varied among different job titles with p < 0.05. Assessing the hand cleaning point, the hand hygiene compliance rate peaked after exposure to blood/body fluid, at 72.8%, and was lowest before interaction with the patients, at 50.1%. Conclusion: The compliance rate of medical staff towards hand hygiene regulations at Friendship Hospital in 2023 needed improvement.